Imaging Guidelines and Recommendations for Diagnosis, Surveillance, and Management of Pediatric CNS and Spinal Tumors - Kapadia, Tejas; Sahu, Arpita; Mahajan, Abhishek; Ahuja, Ankita; Chatterjee, Abhishek; Sahu, Amit; Warade, Anshu; Padashetty, Shubham; Vijan, Antariksh; Chidambaranthan, Natesan; Dasgupta, Archya; Sridhar, Epari; Sahay, Ayushi; Shetty, Prakash; Prasad, Maya; Chinnaswamy, Girish; Moiyadi, Aliasgar; Gupta, Tejpal; Gala, Foram; Sankhe, Shilpa (Indian Journal of Medical and Paediatric Oncology, 2023)
Central nervous system (CNS) tumors are the second most common cause of cancer in children when incidence rates of cancer are estimated according to the Indian population dynamics based on 2011 consensus. As per the estimates, CNS tumors account for 20.1% of cancer burden in children aged between 0 and 14 years and 16.8% when 0 to 19 years age group is considered. The most common pediatric brain tumors are astrocytoma and medulloblastoma followed by other embryonal tumors, craniopharyngioma, and ependymal tumors. The incidence of CNS tumors in children from India is similar to the western high-income countries, other than slightly higher incidence of craniopharyngioma in Indian children.
Keywords: MRI; pediatric brain tumors; protocol; spinal tumor